Sexual function, contraception, relationship, and lifestyle in female medical students - Wallwiener, Christian Wilhelm; Wallwiener, Stephanie; Wallwiener, Markus (Journal of women's health, 2017)
Background: We undertook to study possible determinants of female sexual dysfunction (FSD) in a large cohort of female medical students from German-speaking countries.Methods: We conducted an online questionnaire-based anonymous survey in a cohort of >2600 female medical students enrolled at German-speaking universities. The questionnaire comprised the Female Sexual Function Index (FSFI) plus additional questions regarding contraception, sexual activity, age, height, weight, lifestyle, activity at work, sexuality and emotional interaction with a steady partner, pregnancy history and plans, health problems, and self-acceptance. Data analysis employed descriptive statistics, univariate and multivariate analyses, and standard nonparametric tests.Results: Of the 2612 respondents aged ≤30 years included in the analysis (mean age [standard deviation], 23.5 [2.5] years), 38.7% of the overall cohort and 33.5% of the sexually active subcohort (91.8% of all students) were at risk for FSD (FSFI score <26.55). Multivariate analysis revealed the following significant factors to be associated with the FSFI: alcohol consumption, level of fitness, use of contraception, steady relationship, and self-acceptance (overall cohort and sexually active subcohort); smoking (overall cohort only); and body mass index and activity at work (sexually active subcohort only).Conclusions: Almost 40% of German-speaking female medical students are at risk for FSD. Contraception, smoking, alcohol, steady relationship, physical fitness, and self-acceptance are significantly associated with the FSFI total score. Being in a steady relationship, better physical fitness, higher activity at work, and subjectively positive self-acceptance, in particular, are associated with higher FSFI total scores, that is, with less risk for sexual dysfunction.
Published online:1 Feb 2017
Gesehen am 22.08.2018